An all-in-one theranostic nanoplatform based on upconversion dendritic mesoporous silica nanocomposites for synergistic chemodynamic/photodynamic/gas therapy. Issue 47 (26th November 2020) - Liu, Shikai; Li, Wenting; Dong, Shuming; Zhang, Fangmei; Dong, Yushan; Tian, Boshi; He, Fei; Gai, Shili; Yang, Piaoping
Abstract : A NO-release platform based on upconversion dendritic mesoporous silica nanocomposites was invented for combined imaging-guided synergistic chemodynamic/photodynamic/gas therapy. Abstract : Gasotransmitters with high therapeutic efficacy and biosafety have been drawing the attention of researchers. Nevertheless, how to effectively deliver gases to and precisely control their generation at the lesion as well as integrate them with other therapies to realize precision therapy have remained elusive. Herein, we report a versatile Cu 2+ -initiated nitric oxide (NO) nanocomposite for multimodal imaging-guided synergistic chemodynamic/photodynamic/gas therapy. After the nanomedicine was ingested by tumor cells, the acidic tumor microenvironment accelerated the decomposition of CuO2 and simultaneously triggered the Fenton-like catalytic reaction of Cu 2+ and H2 O2 to produce highly toxic ˙OH. By virtue of the NO generation and glutathione depletion, UMNOCC-PEG can relieve the antioxidant capacity and hypoxia of the tumor to improve the efficiency of chemodynamic therapy (CDT) and photodynamic therapy (PDT). Importantly, NO and reactive oxygen species (ROS) can generate reactive nitrogen species (RNS), which can result in DNA damage, further improving the therapeutic effect (cell apoptosis rate up to 93.4%). Moreover, the inherent properties of lanthanide ions endow UMNOCC-PEG with upconversion luminescence (UCL), CT and MRI trimodal imaging capability, achieving precise cancer treatment. By taking advantage of these features, the strategy developed here may provide a promising application foreground to conquer malignant tumors.